PROSEDUR PENGAJUAN DAN ANALISIS KELAYAKAN PEMBIAYAAN BERBASIS SYARIAH DI BMT UGT SIDOGIRI CAPEM GADANG MALANG : Pendekatan Kualitatif - Nabila Adenina Zidni Maulida; Irawati Irawati; Hilmi Nur Azizah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the procedure for submitting and analyzing the feasibility of sharia-based financing at BMT UGT Sidogiri Capem Gadang Malang. The method used is qualitative with an inductive approach, through in-depth interviews with BMT employees and internal documentation. The results of the study indicate that the procedure for submitting financing includes member registration, initial interviews, filling out forms and completing documents, field surveys, feasibility analysis with the 5C principle (character, ability, capital, guarantee, condition), checking collateral, approval, signing contracts, disbursement of funds, and monitoring the use of funds. The process is carried out effectively, in accordance with sharia principles, and prioritizes caution, thus supporting the sustainability of the institution and empowering the community's economy. In conclusion, the procedure and analysis of the feasibility of financing at BMT UGT Sidogiri Capem Gadang can be a reference for the development of sharia microfinance practices in Indonesia.